Promoting Social Innovation and Solidarity Through Transformative Processes of Thought and Action A Lifetime for Social Change - Tribute to Susanne Elsen - Biesecker, Adelheid; Bragagnolo, Cinzia; Crepaz, Katharina; Friesenhahn, Günter J.; Hofmeister, Sabine; Kiesswetter, Oscar; Lorenz, Walter; Matthies, Aila-Leena; Moulaert, Frank; Nothdurfter, Urban; Piccoli, Alessandra; Scarone, Sabrina; et al. (bu,press, 2023)
Against the background of current crises and fundamental social questions, this edited volume collects contributions that touch upon aspects of social innovation and eco-social transformation in the fields of social work, education, community development and social and solidarity economy. Their common thread and the volume's overall focus is on transformative and transdisciplinary approaches to research and practice - ways Susanne Elsen has encouraged throughout her career - pointing out her forward-looking contribution not only to social work but far beyond. The volume addresses scholars, students, policy makers, and a broader readership interested in tackling current sustainability challenges by innovating solidarity systems and fostering bottom-up processes of eco-social transformation.